Socioeconomic inequalities in mortality due to all causes in the working age population of Poland in 2002 and 2011 - Małgorzata Pikala; Irena Maniecka-Bryła (Nofer Institute of Occupational Medicine, 2017)
Background: The aim of the study was to evaluate the influence of education, marital status, employment status and place of residence on mortality in the working age population of Poland in 2002 and 2011. Material and Methods: All deaths of Poland's inhabitants aged 25-64, in 2002 (N = 97 004) and 2011 (N = 104 598) were analyzed. For individual socio-economic groups standardized mortality rates (SDR) per 100 000 and rate ratio (RR) were calculated. Results: In the group of economically inactive men SDR decreased from 2244.3 in 2002 to 1781.9 in 2011, while in the group of economically active population increased from 253.8 to 298.9 (RR drop from 8.8 to 6). In the group of economically inactive women SDR decreased from 579.5 to 495.2, and among the economically active women population it increased from 78.8 to 90.9 (RR drop from 7.4 to 5.4). In the group of men with higher education SDR decreased from 285.7 to 246, while among men with primary education it increased from 1141 to 1183 (RR increase from 4 to 4.8). In the group of women with higher education SDR decreased from 127.2 to 115.6 and among women with primary education it increased from 375.8 to 423.1 (RR increase from 3 to 3.7). In the group of divorced/separated SDR also increased - from 1521.4 to 1729.8 among men and from 365.5 to 410.8 among women. Conclusions: Future prevention and educational programs should be addressed primarily to the population economically inactive, with primary education and those divorced/separated. Med Pr 2017;68(6):771-778